Há histórias tão verdadeiras que às vezes parece que são inventadas : histórias de crianças e adolescentes acolhidos - Figueiredo, Juliana Gomes de (2012)
It deals with the stories of children and teens received in two shelter houses at the municipality of Vitória-ES. It shows the sheltering situation under the viewpoint of the sheltered individuals, prioritizing their perceptions about their own condition, as well about their familiar relationships and their expectative for the future. It rescues the Brazilian Childhood and Youth history since the colonization till the present time, crossed by the hygienism doctrine and also by the medical-judicial apparatus, as a relief tool of a specific population. It crosses the history of the Brazilian childhood-youth legislation, since the creation of the first Younger s Code till the implementation of the Childs and Teens Statute, in 1990. It utilizes the oral story as methodological tool. Analyses hegemonic practices that create subjectivities, built at the neo-liberal capitalist logic, which blame and hold responsible the families, in general the poor ones, considered unable to create their children within an instituted bourgeois style. It considers the speeches and practices built in those sheltering institutions which arrest the child and teen in their subjective constructions which label, stigmatize and characterize them as unstable which would justify their need of relief. It explains that, although the weakening of their previous familiar entails, the sheltering is not avoiding the formation of new affective nets and the new significance of family, school and their own future, creating other subjectivation modes. It concludes that, at the sheltering house, although the subjective construction which unpower/victimize the received children and teens, there are spaces for the invention of other ways to be and stay under shelter, ways that methods which individualize the human being.